The Complex Association of FcγRIIb With Autoimmune Susceptibility - Verbeek, J. Sjef; Hirose, Sachiko; Nishimura, Hiroyuki (Frontiers in Immunology, 2019)
The complex association of FcγRIIb with autoimmune susceptibility Abstract FcγRIIb is the only inhibitory Fc receptor and controls many aspects of immune and inflammatory responses. The observation 18 years ago that FcγRIIb-/- mice generated by gene targeting in 129 derived ES cells developed severe lupus like disease when backcrossed more than 7 generations into C57BL/6 background initiated extensive research on the genetic basis and functional understanding of this strong autoimmune phenotype. The genomic region in the distal part of Chr1 both in human and mice in which the FcγR gene is located shows a high level of complexity in relation to the susceptibility to SLE. Specific haplotypes of closely linked genes including the FcγRIIb and SLAMF genes are associated with increased susceptibility to SLE both in mice and human. Using forward and reverse genetic approaches including in human GWAS and in mice congenic strains, KO mice, (germline and cell type specific, on different genetic background), knockin mice, overexpressing transgenic mice combined with immunological models such as adoptive transfer of B cells from Ig transgenic mice the genes involved and the causing mutations and their functional alterations were analyzed. In this review the results of this 18 years extensive research are discussed with a focus on (genetically modified) mouse models.